Desdobramentos do Japão: entre vistas de artistas/artesãos no Brasil - Takiguti, Karina Ayumi Ekami [UNIFESP] (2016)
This research presents trajectories of nondescendants of Japaneses that produce works inspired by iconographies or nipponic technics in the contemporary days. Our goal is to show the courses that lead to the creation of those works as well as showing the images, practices and ideas that are transferred and adapted in relations between Brazil and Japan. So in the first part we go through the journey of Remo Nogueira, Horishion, Francis J. Y. Marie, Binho Ribeiro e Lia Menna Barreto, connecting them to other artistic contexts and visual analysis which could be related to their productions. Then we have tried to investigate the mechanisms of assimilation of Japaneses references through the stages: approaching, appropriation and transfiguration, relating them to the ideas of Cecilia Almeida Salles in Gesto Inacabado: processo de criação artística and other authors that have shared the same thoughts.